1987
DOI: 10.1177/016502548701000303
|View full text |Cite
|
Sign up to set email alerts
|

The Early Development of Low-Birthweight Infants: Relationship to Health, Family Status, Family Context, Family Processes, and Parenting

Abstract: This study examines the early development of low birthweight infants and its relationship to five categories of medical and environmental variables: (1) health; (2) family status; (3) family context; (4) family process; and (5) parenting. Results showed that scores on the Bayley Mental Development Index. (MDI) at 18 months were related to all five categories of variables. However, most correlations were only moderate in strength (0.3 to 0.5) and four of the. five categories could be represented by only a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…The HOME was scored by the data collector using observational data and a nondirective interview of the mother. The HOME has been correlated with the developmentally supportive behaviors of mothers (Holditch-Davis, Tesh, Goldman, Miles, & D'Auria, 2000;Tesh & Holditch-Davis, 1997) and with later school performance (Bradley, 1987;Bradley et al, 1994; in ethnically and socioeconomically diverse samples (Bradley et al; Tesh & Holditch-Davis). Test-retest reliabilities for the total HOME scale, when scored at 6 and 12month intervals, have been .76-.77 (Caldwell & Bradley; Holditch-Davis et al; Tesh & Holditch-Davis).…”
Section: Instrumentsmentioning
confidence: 99%
“…The HOME was scored by the data collector using observational data and a nondirective interview of the mother. The HOME has been correlated with the developmentally supportive behaviors of mothers (Holditch-Davis, Tesh, Goldman, Miles, & D'Auria, 2000;Tesh & Holditch-Davis, 1997) and with later school performance (Bradley, 1987;Bradley et al, 1994; in ethnically and socioeconomically diverse samples (Bradley et al; Tesh & Holditch-Davis). Test-retest reliabilities for the total HOME scale, when scored at 6 and 12month intervals, have been .76-.77 (Caldwell & Bradley; Holditch-Davis et al; Tesh & Holditch-Davis).…”
Section: Instrumentsmentioning
confidence: 99%
“…The questionnaire assesses both instrumental and social-emotional support available to the parent. The staff adapted the SSQ from social support measures produced by other researchers (see Lazarus, DeLongis, Folkman, & Gruen, 1985), including one used in our own previous study of low-birthweight children (Bradley, Caldwell, Rock, Casey, & Nelson, 1987). Instrumental support involves the amount of assistance that is available both within and outside the family for completing essential daily activities such as housekeeping, yard maintenance, and child care.…”
Section: Instrumentsmentioning
confidence: 99%
“…Pederson, Evans, Chance, Bento, and Fox (1986) found the degree of maternal maturity and responsiveness to be an important contributor to developm ental progress for low-birthweight infants. Several subscales of the Home Observation for the Measurem ent of the Environment (HOME) inventory, covering social and physical stimulation, have been reported to be signi cantly correlated with the development al status of preterm infants (Bradley, Caldwell, Rock, Cases, & Nelson, 1987;Greenberg & Crnic, 1988;Ross, 1985). Siegel (1982Siegel ( , 1985a and Smith, Smorvik, Sommer, and von Tetzchner (1982) demonstrated that HOME scores were able to account for those cases which had turned out to be false-positives in the prediction of early childhood outcome from perinatal risk conditions.…”
mentioning
confidence: 99%